Służba na rzecz totalitarnego państwa jako przesłanka obniżenia zaopatrzenia emerytalnego funkcjonariuszy zatrudnionych w organach bezpieczeństwa w latach 1944–1990 - Prus, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The paper describes term of service in a totalitarian state as a basis for reducing the pension of officers employed in the security service in the years 1944–1990. The legislators decided to hold liable the officers of the communist political police by reducing their pensions again, 26 years after the transformation. In this aspect, the crucial issue is the concept of service in a totalitarian state. The thesis of the paper is that the qualification of service in a totalitarian state cannot be determined only by formal conditions, that is, the time and place of service, but should also take into account substantive criteria, especially violation of the fundamental rights of individuals by former officers.
Keywords: służba na rzecz totalitarnego państwa; prawo do sądu; emerytura